The Identity of Loyalty To The Surabaya Hero Museum In East Java - Himawan Sardju; Indrianawati Usman; Sri Wahyuni Astuti (Universitas Muhammadiyah Sidoarjo, 2023)
This research is to look for the influence of loyalty identity in the form of perceived value, experience quality and patriotism in museums that have historical value in Surabaya, East Java. The number of respondents was 160 respondents where respondents before visiting the museum had obtained information through social media. The results of data processing show that all the influence tests are said to be significant, both direct and indirect influence tests. The existence of significant influence test results can be stated that the predictor variable of loyalty can be a good antecedent because it is important to be input for the tourism industry which focuses on historical museums, so that managerial implications can help how to manage and provide satisfaction to visitors so that visitors besides feel the good atmosphere, also get the experience and desire to revisit.